2018
DOI: 10.1016/j.dib.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Properties data of phenolic resins synthetized for the impregnation of saturating Kraft paper

Abstract: The quality of decorative laminates boards depends on the impregnation process of Kraft papers with a phenolic resin, which constitute the raw materials for the manufacture of the cores of such boards. In the laminates industries, the properties of resins are adapted via their syntheses, usually by mixing phenol and formaldehyde in a batch, where additives, temperature and stirring parameters can be controlled. Therefore, many possibilities of preparation of phenolic resins exist, that leads to different combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…The penetration behavior of resin into a standard reference decorative paper sheet was investigated using a self‐made penetration time measurement device. The working principle of the device is described in detail in earlier publications 29,30,37,40 . In short, this method is based on exploiting the differences in electrical conductivity between dry and resin‐wetted paper samples.…”
Section: Methodsmentioning
confidence: 99%
“…The penetration behavior of resin into a standard reference decorative paper sheet was investigated using a self‐made penetration time measurement device. The working principle of the device is described in detail in earlier publications 29,30,37,40 . In short, this method is based on exploiting the differences in electrical conductivity between dry and resin‐wetted paper samples.…”
Section: Methodsmentioning
confidence: 99%
“…Chemical shifts are reported in parts per million and referenced to the signals of deuterated solvents. 1 H NMR chemical shifts are reported relative to the signals of tetramethylsilane. The spectra were processed using the MestReNova Lab package (version 12.0.4, MESTRELAB RESEARCH, S.L., Santiago de Compostela, Spain).…”
Section: Measurementsmentioning
confidence: 99%
“…Based on the data obtained from 1 H NMR spectroscopy, it can be concluded that some branched triazine structures insoluble in toluene are formed. Thus, carrying out the reaction in a toluene/isopropanol solvent mixture gives a much cleaner product than in pure toluene medium.…”
Section: Figure 2 Synthesis Of Benzoxazine Monomers Based On Diaminesmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenol‐formaldehyde (phenolic) resins are widely used in construction, 1 electronics 2 and the aerospace sector 3 because of the low cost and relatively high performance, for example, heat and fire resistance 4 . However, phenolic resins have a number of disadvantages that limit their use, for example, the release of volatile substances during curing and the formation of micropores inside the material, which impair the properties of the final products or require autoclave processing to obtain high‐performance material 5 .…”
Section: Introductionmentioning
confidence: 99%